State of the art of helicopter hybrid propulsion - Mercier, C.; Gazzino, M. (My University, 2015)
As done in the car industry, it can be envisaged replacing thermal energy necessary for helicopter propulsion and sustentation by electrical energy. Improvements on electrical technologies allow proposing electrical systems with attractive power to mass ratio to complement the thermal engine providing the mechanical power necessary for the helicopter propulsion. The differences between automotive functions devoted to hybridization and these possible in the case of a helicopter are explained. The different architectures (on turbine or on helicopter side) are reviewed and examples of possible applications on classical helicopters are given, not only the case of AH light helicopter autorotation management improver successfully tested in 2011. The requirements on the electrical system for industrial applications are reviewed: electrical motor and power electronics, cooling systems, energy storage.
Keywords: Engines & Propulsion